Microbiological diagnosis and water addition index of raw milk marketed in the city of Pombal, Paraíba, Brazil - Paiva, Yaroslávia Ferreira; França, Kevison Romulo; Silva, Everton Vieira da; Silva Filho, José Adalberto da; Pereira, Karla Elita Viegas; Araújo, Alfredina dos Santos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The commercialization of milk without heat treatment or sanitary inspection control is prohibited by law in all over the country, but it happens in some small cities. It is important to evaluate the milk in these localities, as it will be consumed by the population. The objective of this study was to evaluate the microbiological diagnosis and the index of water addition in samples of raw milk commercialized in the city of Pombal (PB). Three samples were collected from each of the five commercial sites (A, B, C, D and E) between May and June 2017. They were obtained in sterile containers and evaluated for Coliform parameters at 45ºC (NMP/mL), presence / absence of Salmonella sp. and Escherichia coli, Staphylococcus spp. (UFC/mL) and total count of Mesophyll Aerobic bacteria (CTM) (UFC/mL). The addition rate of water was determined using the Master Classic Milk Analyzer. All samples presented Coliforms at 45ºC (> 110 NMP / mL), presence of Salmonella sp. And Escherichia coli, In addition to high counts of Staphylococcus spp. (3.13 x 10 2 at 2.65 x 10 5 UFC / mL) and CTM (2.30 x 10 4 at 3.91 x 10 5 CFU / mL). Samples from locality B had a water addition index of approximately 5%. We concluded that the raw milk marketed in the city of Pombal (PB) during the period of the research was out of the microbiological standards for all analyzed parameters, besides the existence of fraud by addition of water in the samples of the locality B, being improper for consummation.